(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Ambulatory anaesthesia has become an important component of modern surgical practice due to rapid recovery, early discharge, reduced hospital stay, and improved patient satisfaction. Propofol and sevoflurane are commonly used anaesthetic agents for day-care surgeries because of their favourable pharmacological properties. The present study was conducted to compare the induction and recovery characteristics of propofol and sevoflurane in adult patients undergoing day-care tonsillectomy. Methodology: This randomized prospective study was conducted in the Department of Anaesthesiology, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from January 2025 to December 2025. Eighty patients aged between 13 and 40 years belonging to ASA physical status I and II undergoing elective tonsillectomy and adenoidectomy were included in the study. Patients were randomly allocated into two groups of 40 each. Group P received propofol for induction and maintenance of anaesthesia, while Group S received sevoflurane. Haemodynamic parameters, induction characteristics, Phase I and Phase II recovery profiles, and postoperative complications were assessed and compared. Results: The distribution of Mallampati classification between the two groups was statistically comparable (p=0.28). Mean arterial pressure values were generally lower in the propofol group at all observed time intervals; however, the differences were not statistically significant. The Phase I recovery profile showed no statistically significant difference between Group P and Group S (p=0.29). Similarly, the Phase II recovery profile was also statistically comparable between the groups (p=0.19). Both anaesthetic agents provided satisfactory induction, stable intraoperative conditions, and rapid recovery suitable for ambulatory surgery. Conclusion: Both propofol and sevoflurane were found to be safe and effective anaesthetic agents for day-care adult tonsillectomy. The induction characteristics, haemodynamic responses, and recovery profiles were comparable between the two groups. Hence, both agents can be effectively used in ambulatory tonsillectomy procedures depending on clinical preference and patient suitability.